2019
DOI: 10.1021/acs.analchem.9b02191
|View full text |Cite
|
Sign up to set email alerts
|

Click-Type Protein–DNA Conjugation for Mn2+ Imaging in Living Cells

Abstract: A click-type protein–DNA conjugation, named as MnDDC (Mn2+-activated DCV-DNA conjunction), is presented, where DCV (rep protein of duck circovirus) and its target DNA work as the modular blocks to rapidly and effectively generate Mn2+-dependent and site-specific protein–DNA linkage. On the basis of MnDCC, a fluorescent Mn2+ biosensor composed of DCV and a molecular beacon, was developed for rapid sensing of Mn2+ within 2 min with nanomolar sensitivity. Using the proposed biosensor, not only analysis of Mn2+ in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Excessive Mn 2+ intake by the human body is known to be absorbed by the epidermal cells, transported through the blood circulation and finally enriched in nerve cells . Tracing intracellular Mn 2+ levels in nerve cells can improve our understanding of intracellular Mn 2+ trafficking and the regulation of Mn 2+ homeostasis . Our previous work has demonstrated that the LbCas12a could perform efficient trans-cleavage of FQ reporters in living cells; thus, we further investigated the feasibility of the Cas12a-based assay for probing the intracellular Mn 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive Mn 2+ intake by the human body is known to be absorbed by the epidermal cells, transported through the blood circulation and finally enriched in nerve cells . Tracing intracellular Mn 2+ levels in nerve cells can improve our understanding of intracellular Mn 2+ trafficking and the regulation of Mn 2+ homeostasis . Our previous work has demonstrated that the LbCas12a could perform efficient trans-cleavage of FQ reporters in living cells; thus, we further investigated the feasibility of the Cas12a-based assay for probing the intracellular Mn 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…30 Tracing intracellular Mn 2+ levels in nerve cells can improve our understanding of intracellular Mn 2+ trafficking and the regulation of Mn 2+ homeostasis. 31 Our previous work has demonstrated that the LbCas12a could perform efficient trans-cleavage of FQ reporters in living cells; 11 thus, we further investigated the feasibility of the Cas12a-based assay for probing the intracellular Mn 2+ . The physiological intracellular concentration Mg 2+ is ∼1 mM, and a large part of the physiological intracellular Mg 2+ binds to ribosomes and polynucleotides.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To covalently conjugate CD3‐binding scFv with different DNA frameworks, we exploited a sequence‐directed DNA‐protein conjugation method via HUH endonuclease‐based activity, which could covalently link a DNA oligonucleotide with specific sequence at a specific tyrosine site in the HUH domain tagged protein with a defined stoichiometric ratio (1 : 1) [14] . The conjugation reaction happens rapidly and efficiently, presenting a click chemistry‐like biochemical reaction under the physiological condition [15] . In brief, we first constructed the expression plasmid (Scheme S1) to produce recombinant DCV‐αCD3 protein which contained a DCV domain at the N terminal, a truncated HUH endonuclease derived from duck circovirus (Scheme S2).…”
Section: Resultsmentioning
confidence: 99%
“…[14] The conjugation reaction happens rapidly and efficiently, presenting a click chemistry-like biochemical reaction under the physiological condition. [15] In brief, we first constructed the expression plasmid (Scheme S1) to produce recombinant DCV-αCD3 protein which contained a DCV domain at the N terminal, a truncated HUH endonuclease derived from duck circovirus (Scheme S2). Then, the DCV-αCD3 protein was purified and incubated with the DNA oligonucleotide containing a specific DCVanchoring sequence (AAGTATTACCAGAAA) at their 5' terminal in the presence of Mn 2 + (Figure S1a).…”
Section: The Prototypic Can-te (V10) With Mono-target Antigenmentioning
confidence: 99%